MUTUAL ATTACHMENT BETWEEN SOCIAL WORK STUDENTS AND CLIENTS IN PROFESSIONAL PRACTICE - Bagdonaite-Stelmokiene, Ramune (European Scientific Journal, ESJ, 2015)
The article presents the results of qualitative research carried out in Lithuania. The research focused on the development of mutual attachment between social work students and clients during the professional practice by revealing subjective student experiences. Study participants comprised 53 final-year social work students from one university of Applied Sciences. The use of unstructured reflection as a data collection method enabled students to remember, think over and put their professional practice experiences in writing. Based on the grounded theory data analysis method (Strauss & Corbin, 1990), open, axial and selective coding was applied. Data analysis revealed the conditions necessary for successful mutual relationships between students and clients to emerge, the context of formation of their mutual attachment, the interactions affecting this phenomenon, the conditions preventing its formation as well as the likely consequences of attachment-based relationships between students and clients. The research results revealed that once students successfully adapt to the organization and establish close confidence-based relations with their clients during the social work practice, the mutual attachment between the student and the client is being formed. The attachment is influenced not only by relations between the student and client, but also between the student and the organization’s staff as well as organizational culture. The research results are useful for social work practice. They provide an opportunity to understand the new students’ experiences of relationships formed with different social actors in the practice and their impact on students’ professional and personal change